Isolated Pulmonary Embolism following Shoulder Arthroscopy - Nicole H. Goldhaber; Christopher S. Lee (Case Reports in Orthopedics)
Pulmonary embolism (PE) following shoulder arthroscopy is a rare complication. We present a unique case report of a 43-year-old right-hand dominant female who developed a PE 41 days postoperatively with no associated upper or lower extremity DVT. The patient had minimal preoperative and intraoperative risk factors. Additionally, she had no thromboembolic symptoms postoperatively until 41 days following surgery when she developed sudden right-hand swelling, labored breathing, and abdominal pain. A stat pulmonary computed tomography (CT) angiogram of the chest revealed an acute PE in the right lower lobe, and subsequent extremity ultrasounds showed no upper or lower extremity deep vein thrombosis. After a thorough review of the literature, we present the first documented isolated PE following shoulder arthroscopy. Although rare, sudden development of an isolated PE is possible, and symptoms such as sudden hand swelling, trouble breathing, and systemic symptoms should be evaluated aggressively with a pulmonary CT angiogram given the fact that an extremity ultrasound may be negative for deep vein thrombosis.